2021
DOI: 10.1186/s41181-021-00126-z
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in the automated synthesis of 6-[18F]Fluoro-L-DOPA

Abstract: The neurotracer 6-[18F] FDOPA has been, for many years, a powerful tool in PET imaging of neuropsychiatric diseases, movement disorders and brain malignancies. More recently, it also demonstrated good results in the diagnosis of other malignancies such as neuroendocrine tumours, pheochromocytoma or pancreatic adenocarcinoma.The multiple clinical applications of this tracer fostered a very strong interest in the development of new and improved methods for its radiosynthesis. The no-carrier-added nucleophilic 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…6-[ 18 F] uoro-L-DOPA [3], since its rst clinical application in the imaging of dopaminergic pathways of human brain [4], has been used to report a wide variety of diseases [5], including neuro-oncology [6,7], endocrinology [8], and Parkinson's disease [9,10], As a result, a range of methods have been developed for this valuable radiotracer. [11,12] The rst synthesis of radioactive L-DOPA (5-[ 18 F] uoro-L-DOPA) was accomplished by Firnau and co-workers in 1973 using diazonium uoroborate compound as precursor [13]. The same lab later reported the synthesis of this radiotracer by the reaction of L-DOPA and [ 18 F]F 2 , which afforded only a mixture of 2-, 5-and [ 18 F] uoro-L-DOPA [14].…”
Section: Introductionmentioning
confidence: 99%
“…6-[ 18 F] uoro-L-DOPA [3], since its rst clinical application in the imaging of dopaminergic pathways of human brain [4], has been used to report a wide variety of diseases [5], including neuro-oncology [6,7], endocrinology [8], and Parkinson's disease [9,10], As a result, a range of methods have been developed for this valuable radiotracer. [11,12] The rst synthesis of radioactive L-DOPA (5-[ 18 F] uoro-L-DOPA) was accomplished by Firnau and co-workers in 1973 using diazonium uoroborate compound as precursor [13]. The same lab later reported the synthesis of this radiotracer by the reaction of L-DOPA and [ 18 F]F 2 , which afforded only a mixture of 2-, 5-and [ 18 F] uoro-L-DOPA [14].…”
Section: Introductionmentioning
confidence: 99%
“…11−18 Given its advantageous diagnostic potential, since the 1980s, diverse methods have been developed for 6-[ 18 F]FDOPA synthesis, each with unique advantages and limitations (Scheme S1). 8,19 However, the complexity of current methods, involving expensive automated modules and HPLC instruments, impedes the widespread adoption of 6-[ 18 F]FDOPA. Therefore, simplified synthetic protocols are still in high demand for the cGMP synthesis of 6-[ 18 F]-FDOPA.…”
mentioning
confidence: 99%
“…6-[ 18 F]­FDOPA, an FDA-approved radiopharmaceutical agent, finds extensive use in PET imaging for visualizing and measuring dopaminergic neuron activity . Its application extends beyond managing neurologic disorders like Parkinson’s disease, , with ongoing research and clinical trials in oncology. Given its advantageous diagnostic potential, since the 1980s, diverse methods have been developed for 6-[ 18 F]­FDOPA synthesis, each with unique advantages and limitations (Scheme S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article (Neves et al 2021 ), some errors were identified in the article text:…”
mentioning
confidence: 99%